Simultaneous Multi-Adulterant Detection in Milk Using an In-house Developed Multiplexed Microfluidic Paper-Based Analytical Device (M-µPAD) - Jannat Ahsan (22466530) (2025)
Milk adulteration poses a significant challenge in developing countries, impacting food safety and public health. This study introduces a multiplexed microfluidic paper-based analytical device (M-µPAD) for rapid and simultaneous detection of multiple milk adulterants. The M-µPAD, fabricated using readily available materials like filter paper and wax crayons, eliminates the need for specialized equipment. The device demonstrates linear relationships between colorimetric response and adulterant concentration for urea (10–200 mg/dL), starch (20-1000 mg/dL), and detergent (100–3000 mg/dL), with detection limits of 11.1, 22.4, and 120.8 mg/dL, respectively. Requiring only 40 µL of reagents and 80 µL of milk sample, the M-µPAD achieves over 95% accuracy and reproducibility with RSD values below 4%. This affordable, in-house fabricated platform offers a promising solution for milk quality assessment in resource-limited settings, addressing the need for accessible and efficient adulterant detection methods. Other Information Published in: Sensing and Imaging License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11220-025-00580-y